Report of the Resident Representative for India January-June 1953 India's Development and her Need for External Aid - Planning Commission (Planning Commission, 1953)
India’s five-year plan of development aims at introducing the dynamic elements of growth into an economy which by and large has developed at a relatively very slow pace. the Indian economy in the past has perhaps been less static than most other economies in Asia. Some of the elements of its growth had been provided in the past by India's membership in the British Empire which first developed her raw materials like cotton and later, under the stress of two world wars, her major industries like steel, jute, cotton, cement and coal.
India's Development and Her Need for External Aid